El poblamiento prehistórico del campo de Gibraltar - Mas Cornellá, Martí; Ripoll López, Sergio; Torra Colell, G.; Jordá Pardo, Jesús Francisco; Gavilán Ceballos, Beatriz; Vera Rodríguez, J.C. (Espacio Tiempo y Forma. Serie I, Prehistoria y Arqueología, 1996)
-